The future of management - Hamel, Gary. (Boston, Mass. : Harvard Business School Press, 2007)
"In The Future of Management, world-renowned business sage Gary Hamel argues that organizations need bold management innovation now more than ever. The current management model - centered on control and efficiency - no longer suffices in a world where adaptability and creativity drive business success." "In his most provocative book to date, Hamel takes aim at the legacy beliefs preventing twenty-first-century companies from surmounting new challenges. With incisive analysis and vivid illustrations, he explains how to turn your company into a serial management innovator."--Jacket.
The end of management? -- The ultimate advantage -- An agenda for management innovation -- Creating a community of purpose -- Building an innovation democracy -- Aiming for an evolutionary advantage -- Escaping the shackles -- Embracing new principles -- Learning from the fringe -- Becoming a management innovator -- Building the future of management.
Includes bibliographical references (pages 257-263) and index.
Description based on print version record.
Keywords: Management; Technological innovations -- Management; Knowledge management; Gestion; Innovations -- Gestion; Gestion des connaissances; Administração; Administração de inovações tecnológicas; Gestão do conhecimento; Management; Organisationswandel; Innovationsprozess; Innovationsmanagement; Unternehmensführung -- Wandel; Management; Technischer Fortschritt; Führungstechnik; Knowledge management; Management; Technological innovations -- Management; Innovations - Gestion; Innovationsprozess; Management; Organisationswandel; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books